Money and inflation in inflation-targeting regimes: New evidence from time-frequency analysis - Maciej Ryczkowski (Journal of Applied Economics, 2021)
This article investigates the post-1990 link between broad money growth and inflation in 16 full-fledged inflation-targeting regimes and four benchmark non-inflation-targeting regimes. This study employs the Christiano-Fitzgerald band-pass filter and continuous wavelet transform to analyze the co-movements across operational horizons and time. According to the band-pass filtering techniques, the link between money growth and inflation was weak and statistically nonsignificant over the investigated period: from 1990 onwards. The wavelet analysis demonstrated significant causality running from money growth to inflation, and strong significant co-movements between the two variables around the Great Recession at a typical business cycle frequency. This finding suggests that policymakers may need to respond to the short-run surges in money growth by reducing money growth rates. The empirical findings support the proposal that policymakers should return to a monetary framework that controls the money supply.
Keywords: 330; Money and inflation; inflation targeting; quantity theory of money; money demand; wavelets